2010
DOI: 10.1093/jaoac/93.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Validation Procedures for Quantitative Food Allergen ELISA Methods: Community Guidance and Best Practices

Abstract: This document provides supplemental guidance on specifications for the development and implementation of studies to validate the performance characteristics of quantitative ELISA methods for the determination of food allergens. It is intended as a companion document to other existing publications on method validation. The guidance is divided into two sections: information to be provided by the method developer on various characteristics of the method, and implementation of a multilaboratory validation study. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 0 publications
4
65
1
1
Order By: Relevance
“…Further the trial was intended to identify which contamination levels can be reliably detected and if these levels correspond to relevant concentrations for food safety management, even though no legal limits exist at this time. Based on these findings a validation study would be organized according to the harmonized validation protocol (Abbott et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further the trial was intended to identify which contamination levels can be reliably detected and if these levels correspond to relevant concentrations for food safety management, even though no legal limits exist at this time. Based on these findings a validation study would be organized according to the harmonized validation protocol (Abbott et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A guidance protocol on method validation and testing the performance characteristics of quantitative food allergen ELISA methods was recently published under the auspices of the AOAC Presidential Task Force on Food Allergens and with the active contribution of the MoniQA Allergen Working Group (Abbott et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme‐linked immunosorbent assays (ELISAs) are the favoured analytical approach for the food industry because they can detect allergen residues in a highly specific and sensitive manner . Commercial ELISA kits exist for many of the priority allergenic foods, but questions remain about their reliability with most kits not being validated according to the consensus approach . For example, a recent international study demonstrated that only one egg kit accurately determined egg protein at 3 mg/kg and only one milk (casein) kit accurately determined milk protein at 6 and 15 mg/kg .…”
Section: The Analytical and Food Scientists’ Perspectivesmentioning
confidence: 99%
“…Reference materials that are representative of the target analyte are essential prerequisites for calibrating and assuring the accuracy of analytical methods. They form the basis for method establishment and validation, proficiency tests, and verification of the comparability between different methods and laboratories (161)(162)(163). The use of appropriate reference materials was recently shown to efficiently reduce the disparity of gluten analysis between different commercial kits (157).…”
Section: A Five Cultivar Wheat Blend Is Suitable For New Reference Mamentioning
confidence: 99%
“…Performance criteria include the correct setup and statistical evaluation of validation studies (161,170,171) as well as the fulfillment of the requirements for standard method performance (172). The minimal performance requirements set in AOAC SMPR 2016.002 (169) for whole egg, milk, peanut and hazelnut can be adapted to gluten.…”
Section: Performance Criteriamentioning
confidence: 99%